Strengthening fiscal discipline in the EMU in a market-led approach. - Cui, Cong. (2013)
The undergoing eurozone crisis highlighted the importance of an effective mechanism to strengthen the fiscal discipline in the EMU. After looking into three mainstream approaches, the author believes that the market-led approach, which applies the market automatic adjustment system to strengthen the fiscal discipline, is the most promising one. This article then focuses on finding out the feasibility of this market-led approach and what need to be done to improve it.